A novel vaccine adjuvant based on straight polyacrylate potentiates vaccine-induced humoral and cellular immunity in cynomolgus macaques. Issue 7 (3rd July 2021) - Pavot, Vincent; Bisceglia, Hélène; Guillaume, Florine; Montano, Sandrine; Zhang, Linong; Boudet, Florence; Haensler, Jean
ABSTRACT: Adjuvants are central to the efficacy of subunit vaccines. Although several new adjuvants have been approved in human vaccines over the last decade, the panel of adjuvants in licensed human vaccines remains small. There is still a need for novel adjuvants that can be safely used in humans, easy to source and to formulate with a wide range of antigens and would be broadly applicable to a wide range of vaccines. In this article, using the Respiratory Syncytial Virus (RSV) nanoparticulate prefusion F model antigen developed by Sanofi, we demonstrate in the macaque model that the polyacrylate (PAA)-based adjuvant SPA09 is well tolerated and increases vaccine antigen-specific humoral immunity (sustained neutralizing antibodies, memory B cells and mucosal immunity) and elicits strong TH 1-type responses (based on IFNγ and IL-2 ELISpots) in a dose-dependent manner. These data warrant further development of the SPA09 adjuvant for evaluation in clinical trials.